A recuperação intensiva do Ensino Fundamental Ciclo II: uma análise da prática pedagógica do professor de matemática - Ambrosio, Ana Cristina da Silva [UNESP] (2015)
This paper reports the results of a Master thesis developed next to the Graduate Program in Education UNESP - Presidente Prudente, linked to the research line Formative Processes and Practices in Education, with the main objective of describing and analyzing the teaching process practiced by mathematics teachers of Intensive Recovery classes of elementary school cycle II, in the state system of Presidente Prudente, with a view to improving student learning, that is, to see how this educational resource has fulfilled the role of collaborate for the student to overcome their difficulties, helping them to actual construction / acquisition of knowledge. The relevance of this problem is based on the institution of the Continued Progression in the state public schools, which provides an educational organization in the form of cycles without failure, which results in classes with students at different levels of knowledge, constituting the recovery as a key mechanism to ensure that the end of the cycle all students achieve better levels of learning. For the research selected five Mathematics teachers of the class's Intensive Recovery 7th year of primary school, working in five different public schools, in which we conduct observation in their classes and then one semi-structured interviews in which teachers justified their practices. We chose a qualitative approach because our main concern was the teaching process, not just the result. We started making a documentary analysis of legislation related to strengthening and rehabilitation of learning in Brazilian public schools, with emphasis on the State of São Paulo, since 1971...